2005
DOI: 10.4049/jimmunol.175.7.4715
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Extracellular Matrix Proteoglycans Decorin and Biglycan with C1q and Collectins

Abstract: Decorin and biglycan are closely related abundant extracellular matrix proteoglycans that have been shown to bind to C1q. Given the overall structural similarities between C1q and mannose-binding lectin (MBL), the two key recognition molecules of the classical and the lectin complement pathways, respectively, we have examined functional consequences of the interaction of C1q and MBL with decorin and biglycan. Recombinant forms of human decorin and biglycan bound C1q via both collagen and globular domains and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 31 publications
4
117
0
2
Order By: Relevance
“…We found that SG bound to the immobilized collagen-like stalk domain of C1q in a similar manner as biglycan (BGN) used as a positive control [23]. As reported previously [20], the negative control fibromodulin (FM) did not bind C1q stalks (Fig.…”
Section: Sg Binds To C1q Stalkssupporting
confidence: 82%
See 1 more Smart Citation
“…We found that SG bound to the immobilized collagen-like stalk domain of C1q in a similar manner as biglycan (BGN) used as a positive control [23]. As reported previously [20], the negative control fibromodulin (FM) did not bind C1q stalks (Fig.…”
Section: Sg Binds To C1q Stalkssupporting
confidence: 82%
“…4D). Decorin, a proteoglycan that has previously been shown to interact with MBL [23], was used as the positive control. We also confirmed that SG bound MBL directly from NHS ( Fig.…”
Section: Sg Binds To C1q and Mblmentioning
confidence: 99%
“…[33][34][35][36] It is therefore noteworthy that decorin has been shown to act as a proinflammatory factor and is produced at sites of inflammation. 18,[37][38][39][40][41] In contrast, Decorin, obesity and type 2 diabetes K Bolton et al decorin has also been reported to bind and inhibit the proinflammatory activity of the complement protein C1q 42 and has been hypothesized to antagonize C1q-induced insulin resistance in adipose tissue that is associated with obesity. 16 These observations indicate that decorin may play a role in inflammation associated with obesity in adipose tissue; however, this is likely to be a complex interaction between pro-and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…The proteoglycans decorin and biglycan can inhibit the classic pathway directly through binding and inhibition of C1q, whereas biglycan inhibits the MBL pathway by inactivating MBL (121). Decorin and biglycan show further inhibition of complement by preventing C1q binding to human umbilical vein endothelial cells and U937 cells, with biglycan further able to inhibit C1q-mediated release of inflammatory monocyte chemoattractant peptide-1 and IL-8 from human umbilical vein endothelial cells (121).…”
Section: Complement Proteins Reorganize Intercellular and Extracellulmentioning
confidence: 99%